Assessment of drought resistance in sorghum CMS lines based on various sterility sources - O. P. Kibalnik; T. V. Larina; O. B. Kameneva; D. S. Semin (Труды по прикладной ботанике, генетике и селекции)
Background. Global climate changes have recently led to a more frequent occurrence of adverse factors and a decrease in the productivity of major crops. Sorghum is a highly drought-resistant crop that can tolerate long-term soil and air droughts with much lower harvest losses than wheat or barley. It is important to understand physiological mechanisms affecting drought tolerance when breeding efforts are aimed at improving the adaptability to abiotic conditions and productivity of sorghum hybrids.Materials and methods. Twenty sterile lines of grain sorghum with 8 types of CMS were studied in 2019 and 2020 in the arid conditions of Saratov Province. Indicators of the leaf water regime were assessed according to VIR’s guidelines. Statistical processing of the research results was performed using the AGROS 2.09 software.Results. The indicators of the leaf water regime that reflected differentiated responses of the CMS-line plants to the prevailing water and temperature stressors during the critical flowering period for sorghum were analyzed. Four CMS lines were identified according to the chosen set of indicators: they manifested 71.13–72.02% of total water content, 5.26–9.08% of water deficit, and 57.40–83.17% of water retention capacity on average for the two years of research. For the first time, the effect of CMS in sorghum on the manifestation of water regime indicators was registered. In isonuclear CMS lines, the greatest effect on drought resistance was shown by cytoplasm A3 versus A4 (with the Zheltozernoe 10 genome), cytoplasm A5 versus A1 (with the Karlik 4v genome), and M35-1A versus the analog on cytoplasm 9E (with the Pischevoe 614 genome).Conclusion. It is shown that genetically different types of sterility can be used in breeding practice to increase the resistance to abiotic stressors in components of F1 crosses and hybrids.